2021
DOI: 10.1186/s12957-021-02409-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel glycolysis-related signature to predict the prognosis of patients with breast cancer

Abstract: Background Breast cancer (BC) has a high incidence and mortality rate in females. Its conventional clinical characteristics are far from accurate for the prediction of individual outcomes. Therefore, we aimed to develop a novel signature to predict the survival of patients with BC. Methods We analyzed the data of a training cohort from the Cancer Genome Atlas (TCGA) database and a validation cohort from the Gene Expression Omnibus (GEO) database. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Both glycolysis and oxidative stress are demonstrated to be activated in BC tissues [ 20 , 25 ]. Herein, the result of GSEA implied that both glycolysis and response to oxidative stress were regulated by LINC00092 in BC tissues ( Figure 4(a) ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both glycolysis and oxidative stress are demonstrated to be activated in BC tissues [ 20 , 25 ]. Herein, the result of GSEA implied that both glycolysis and response to oxidative stress were regulated by LINC00092 in BC tissues ( Figure 4(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…As the main manner for BC cells to produce ATP, glycolysis is essential for BC growth [ 20 ]. Earlier literature reported that even in aerobic environment, BC cells still will choose glycolysis as the main manner for energy supplement [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2F). To comprehensively analyze the prognostic ability of IL score, four risk models [36][37][38][39] from previous studies were collected to compare with the prognostic prediction capacity. The landscape of clinicopathological features in the risk model.…”
Section: Validation and Comparison Of Il Scorementioning
confidence: 99%
“…A gene expression signature consisting with several genetic markers might improve the specificity and sensitivity of prediction for GC. Some studies using data from public databases have also shown that glycolysis-related genes can predict the prognosis of cancer patients, including those with clear cell renal cell carcinoma ( 11 ), lung adenocarcinoma ( 12 ), hepatocellular carcinoma ( 13 ), breast cancer ( 14 , 15 ), ovarian cancer ( 16 ), and colorectal cancer ( 17 ). Additionally, recent research has shown that glycolysis-related genes might be used to effectively assess the prognosis of GC patients ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%